PENERAPAN METODE PETUALANGAN MAHARAJA TERHADAP KEMAMPUAN MEMBACA ANAK USIA DINI KELOMPOK B DI PAUD AL-HIKMAH - Rani Rismawati; Ilham Ramadhan; Ema Marhamah (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
Reading proficiency is a crucial component of language development that needs to be nurtured appropriately, aligning with the stages of children's reading growth. One effective approach to enhancing children's reading skills is the Metode Petualangan Maharaja. This method is designed to stimulate reading abilities through the use of diverse tools such as flashcards and games like snakes and ladders. At its core, this method integrates reading instruction with the natural developmental needs of children, emphasizing learning through play. Therefore, this study aims to: (1) explore the implementation process of the Metode Petualangan Maharaja in improving reading skills among Group B students at PAUD Al-Hikmah, (2) examine the impact of this method on the reading abilities of young learners at PAUD Al-Hikmah Group B, and (3) identify the supporting and hindering factors in applying the Metode Petualangan Maharaja at PAUD Al-Hikmah. This research employs a qualitative descriptive approach, utilizing field research conducted at PAUD Al-Hikmah, an institution that has adopted this method. The study was carried out over two months, from July to August. Data collection techniques included observation, interviews, and document analysis. The research process involved extensive data gathering from multiple sources to obtain comprehensive and detailed insights into the implementation of the Metode Petualangan Maharaja at PAUD Al-Hikmah. The findings reveal that the implementation of the Metode Petualangan Maharaja in Group B at PAUD Al-Hikmah follows structured stages, including planning, execution, and child assessment. The method has positively impacted children's reading abilities, as evidenced by noticeable improvements and increased motivation among students to engage in reading. Key supporting factors for the method's success include the principal's support, the teachers' pedagogical skills, and the children's inherent potential. On the other hand, challenges such as insufficient facilities and parental misconceptions about learning methods have hindered its effectiveness. In conclusion, the Metode Petualangan Maharaja has demonstrated a significant positive influence on the reading abilities of students at PAUD Al-Hikmah, highlighting its potential as an effective educational tool for early childhood reading development.